Decrease in recreational fisher compliance during the COVID-19 pandemic: the case of Rockfish Conservation Areas. (22nd September 2022) - Ban, Natalie C; Miltner, Chessi; Matthews, Charlotte; Ankenman, Madeleine; Stelte, Sarah; Haggarty, Dana; Davies, Hailey L; Venturelli, Paul A; Juanes, Francis
Abstract: Little is known about the effect of the COVID-19 pandemic on recreational fisheries compliance. Starting in 2015, we monitored recreational fishing activity in Rockfish Conservation Areas (RCAs) with trail cameras overlooking RCAs around Galiano Island, Canada. We also carried out in-person surveys with recreational fishers at marinas and docks to assess recreational fisher compliance with RCAs. Questions included asking fishers whether they had accidentally or intentionally fished inside RCAs with prohibited techniques in the past two years. The number of suspected or confirmed angling incidents that we observed on the trail cameras declined steadily from 2015 to 2019, and then increased significantly during the pandemic to the highest levels seen during our eight years of data collection. The number of fishers who admitted to intentionally or accidentally fishing in RCAs in the past two years with prohibited gears did not change during the pandemic, although there was an apparent but not statistically significant increase in the number of respondents who personally knew someone who intentionally fished in RCAs. Our study corroborates other research that showed a response of pandemic lockdowns on illegal activities. High non-compliance highlights the ongoing need for education, outreach, and increased enforcement.